PENGARUH PENERAPAN E-FILING DAN SOSIALISASI PERPAJAKAN DI MASA PANDEMI COVID-19 TERHADAP KEPATUHAN PELAPORAN SPT PPH 21 PADA PEGAWAI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) BANTEN - Rizki Maulida Junita; Nani Rohaeni; Amyati Amyati (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
Taxpayer compliance is important for the state to maintain a source of state revenue. This study aims to determine the effect of the implementation of e-filing and  socialization of taxation in the Covid-19 pandemic period on SPT PPh 21 reporting compliance for Balai Pengkajian Teknologi Pertanian (BPTP) Banten Employees partially and simultaneously. The research used descriptive method, conducted in the Balai Pengkajian Teknologi Pertanian (BPTP) Banten by taking a sample of 70 respondents  using a purposive sampling technique. Collecting data by observation and questionnaires. The data analysis technique used in this study consisted of statistical description, classical assumption test, multiple linear regression analysis, coefficient of determination and statistical hypotheses. The results this study indicate that the application of e-Filing has a positive effect on reporting compliance with SPT PPh 21 having a value of tcount > ttable (2.148>1.999) with a significant value of 0.036. Tax socialization has a positive effect on reporting compliance with SPT PPh 21 having a value of tcount > ttable (7.433>1.999) with a significant value of 0.000. The implementation of e-Filing and tax socialization has a positive and significant effect on reporting compliance with SPT PPh 21 with a value of Fcount>Ftable (127.094>3.15).